Pharmacokinetics of once-daily boosted elvitegravir when administered in combination with acid-reducing agents - Ramanathan, Srinivasan; Mathias, Anita; Wei, Xuelian; Shen, Gong; Koziara, Joanna; Cheng, Andrew; Kearney, Brian P (Journal of acquired immune deficiency syndromes (1999), 2013)
Acid-reducing agents are commonly used co-medications by HIV-1-infected patients receiving antiretroviral treatment. The effects of various representative acid-reducing agents on the pharmacokinetics (PK) of boosted elvitegravir were evaluated by 1-way interaction in 4 studies. Healthy subjects received ritonavir-boosted elvitegravir (EVG/r; 50/100 mg QD) administered alone or with antacid simultaneously in Study 1, staggered (±2 or ±4 hours) or with omeprazole in Study 2; Studies 3 and 4 evaluated cobicistat-boosted elvitegravir (EVG/co; 150/150 mg QD) administered simultaneously or staggered (+12 hours) with famotidine or omeprazole. Lack of PK alteration was defined as 90% confidence intervals about the geometric least squares means ratio (coadministration:alone) being within 70%-143% for elvitegravir Cmax (maximum concentration), Ctau (trough), and AUCtau (area under plasma concentration-time curve; 0-24 hours); cobicistat PK were explored. EVG exposures were 40%-50% lower upon simultaneous dosing of EVG/r and antacids, probably due to local complexation with cations in gastrointestinal tract, and were unaffected with ≥2 hours staggered dosing. No relevant drug interactions were observed between EVG/co and famotidine or between EVG/r or EVG/co and omeprazole, indicating the absence of a broader pH effect on boosted EVG PK. In all studies, study treatments were well tolerated, with adverse events being generally mild to moderate in severity and primarily gastrointestinal disorders. There are no clinically relevant interactions between boosted elvitegravir, and thus elvitegravir/cobicistat/emtricitabine/tenofovir DF single-tablet regimen, and H2-receptor antagonists or proton pump inhibitors; staggered antacid administration by ≥2 hours is recommended.